α Li SCATTERING IN THE FRAMEWORK OF THREE PARTICLE MODEL - Kabatayeva, R. S.; Zhusupov, M. A.; Kukulin, V. I.; Rubtsova, О. А. (Recent Contributions to Physics, 2011)
There is a consideration of α -particles scattering from weakly bound cluster nucleus 6Li in the framework of three cluster α+ α+ ( d ) model in the present work. Continuum α − d states are projected on the finite basis of stationary wave packets what allows to lead the total problem of three bodies to a problem of bound channels. There are represented the results of 6 α Li -scattering differential cross sections calculations in the framework of three particle model and comparison with other authors.
Keywords: scattering